1988
DOI: 10.1080/00039896.1988.9935850
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Lung Cancer in Xuan Wei, China: Current Progress, Issues, and Research Strategies

Abstract: In Xuan Wei, a rural Chinese county of about one million people, females' annual lung cancer mortality is China's highest, and males' is among China's highest. Xuan Wei's very high indoor air pollution levels (sometimes exceeding 20 mg/m3), residentially stable population, relatively uncomplicated lifestyle, and wide geographic variation in lung cancer mortality render it highly amenable to quantitative, interdisciplinary investigation of chemical carcinogens due to indoor air pollution. To date, epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…Our results show that portable stove use was significantly associated with decreased lung cancer mortality risk in both male and female lifetime smoky coal users. This study was performed in a geographically restricted population with minimal industrial and automotive air pollution exposures (Mumford et al, 1987), in which, nearly all women cook (Chapman et al, 1988). Even though most men smoke, similar results in stratified analyses by male participants and female participants serve to increase confidence in the reduction in lung cancer mortality observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that portable stove use was significantly associated with decreased lung cancer mortality risk in both male and female lifetime smoky coal users. This study was performed in a geographically restricted population with minimal industrial and automotive air pollution exposures (Mumford et al, 1987), in which, nearly all women cook (Chapman et al, 1988). Even though most men smoke, similar results in stratified analyses by male participants and female participants serve to increase confidence in the reduction in lung cancer mortality observed.…”
Section: Discussionmentioning
confidence: 99%
“…Xuanwei, China, presents a unique opportunity for investigating in-home coal smoke exposures because it has the highest prevalence of lung cancer in China and the population-attributable risk proportion of coal burning for lung cancer is over 90% (Lan and He, 2004). Lung cancer mortality rates are similar in men and women in Xuanwei, even though nearly all women and few men cook, whereas most men and nearly no women smoke tobacco (Mumford et al, 1987;Chapman et al, 1988). Indoor air pollution in Xuanwei from domestic fuel combustion for most residents is burning smoky coal (bituminous coal), with some burning smokeless coal (anthracite coal).…”
mentioning
confidence: 99%
“…The age-adjusted lung cancer mortality rates for men and women in Xuan Wei are 27.7 and 25.3 per 100 000, respectively (5). The similarity of lung cancer rates in men and women is of considerable interest because almost all women are non-smokers (6). In Xuan Wei, nearly all women and few men cook, whereas most men and nearly no women smoke tobacco (6).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of lung cancer rates in men and women is of considerable interest because almost all women are non-smokers (6). In Xuan Wei, nearly all women and few men cook, whereas most men and nearly no women smoke tobacco (6). The primary source of indoor air pollution in Xuan Wei is smoke from domestic fuel combustion for heating and cooking with most residents burning smoky coal (bituminous coal) and some using smokeless coal (anthracite coal).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have illustrated that the main cause of high mortality of lung cancer is indoor air pollution caused by the use of smoky coal and unimproved stoves [2][3][4][5]. Carcinogenic substances produced in the process of coal combustion are PAHs, including Benzopyrene [6], particulate matter and quartz [7]. Animal experiments have also demonstrated that combustion emissions are carcinogenic to mice [8].…”
Section: Introductionmentioning
confidence: 99%